2020
DOI: 10.48550/arxiv.2007.10712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On Analyzing Antisocial Behaviors Amid COVID-19 Pandemic

Abstract: The COVID-19 pandemic has developed to be more than a bio-crisis as global news has reported a sharp rise in xenophobia and discrimination in both online and offline communities. Such toxic behaviors take a heavy toll on society, especially during these daunting times. Despite the gravity of the issue, very few studies have studied online antisocial behaviors amid the COVID-19 pandemic. In this paper, we fill the research gap by collecting and annotating a large dataset of over 40 million COVID-19 related twee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A recent work showed how the anti-social behavior on social media during COVID-19 led to the spread of hate speech. Awal et al [15] coined the term, 'disability hate speech' and showed its social, cultural and political contexts. Ziems et al [16] explained how COVID-19 tweets increased racism, hate, and xenophobia in social media.…”
Section: Related Workmentioning
confidence: 99%
“…A recent work showed how the anti-social behavior on social media during COVID-19 led to the spread of hate speech. Awal et al [15] coined the term, 'disability hate speech' and showed its social, cultural and political contexts. Ziems et al [16] explained how COVID-19 tweets increased racism, hate, and xenophobia in social media.…”
Section: Related Workmentioning
confidence: 99%
“…2). A study on online antisocial activity indicated increased sinophobic sentiment (Schild et al, 2020) and increased hate speech directed at vulnerable groups as well as xenophobia (Awal et al, 2020). While these studies do not necessarily use the same definition of anti-social behaviour referred to here, they give a useful indication of related research.…”
Section: Asb In the Pandemicmentioning
confidence: 89%
“…3, this suggests that Gettr as a whole is generally representative of the US far-right. These results suggest that the ability to mention one's political opponents on Twitter is part of the reason that the matched cohort are more toxic on Twitter than they are on Gettr where direct interactions with political opponents are not possible [61,62].…”
Section: Content Toxicity and Twitter Mentionsmentioning
confidence: 96%